2000
DOI: 10.1103/physrevb.62.10774
|View full text |Cite
|
Sign up to set email alerts
|

Emittance fluctuations in a mesoscopic diffusive conductor

Abstract: We report a first principles analysis of low frequency dynamic conductance fluctuations for disordered two-dimensional mesoscopic conductors. In the transport regime where dc conductance shows the familiar universal conductance fluctuations, we discovered that the low frequency emittance also fluctuates with an amplitude that is independent of the impurity scattering strength, showing a degree of generic behavior. When the impurity density is increased such that the dynamic response of the conductor changes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Whenever the transmission of carriers between two contacts predominates the reflection, the associated emittance element changes sing and behaves inductance-like. This type of cross over behavior for diagonal element of emittance ν αα (taking into account the Coulomb interaction of electrons inside the sample) was found in 14 where they study the distribution function (DF) of emittance. They have found that in the range of weak disorder, when the system is still conducive the DF is Gaussian-like.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Whenever the transmission of carriers between two contacts predominates the reflection, the associated emittance element changes sing and behaves inductance-like. This type of cross over behavior for diagonal element of emittance ν αα (taking into account the Coulomb interaction of electrons inside the sample) was found in 14 where they study the distribution function (DF) of emittance. They have found that in the range of weak disorder, when the system is still conducive the DF is Gaussian-like.…”
Section: Introductionmentioning
confidence: 68%
“…This type of crossover behavior for the diagonal element of emittance ␣␣ ͑taking into account the Coulomb interaction of electrons inside the sample͒ was found in Ref. 17, where the authors studied the distribution function ͑DF͒ of emittance. They found that in the range of weak disorder, when the system is still conductive, the DF is Gaussian-like.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…For a chaotic QD, the emittance is also positive from the calculation of random matrix theory [5], showing capacitive-like response. For a disordered twodimensional (2D) waveguide, De Jesus et al have calculated the emittance distribution using a continuous model [10]. The emittance distribution is Gaussian at weak disorder and there is a crossover to a non-Gaussian distribution with a tail in the negative emittance region at strong disorder.…”
mentioning
confidence: 99%